In situ FTIR spectra investigation of the photocatalytic degradation of gaseous toluene over a novel hedgehog-like CaFe2O4 hollow-structured materials - Yin, Zhifan; Liu, Baojun; Fan, Shiying; Wang, Penglei; Wang, Xinyang; Long, Dan; Zhang, Long; Yang, Xudong; Li, Xinyong (Catalysis communications, 2019)
A novel hedgehog-like CaFe2O4 hollow microspheres was successfully fabricated by a simple template-assisted method with post-heat treatment. Especially, the hollow architecture was assembled by the nanorods, the surface areas could reach 111.5 m2·g−1. Due to the enhanced light scattering by the hollow architecture, the effective charges separation by the assembled nanorods and the strong catalytic oxidizing performances by the Fe-base spinel material, the hedgehog-like CaFe2O4 catalysts showed marvelous catalytic performance for gaseous toluene degradation. Besides, by in situ FTIR technique, the degradation mechanism of gaseous toluene was clarified clearly based on the detected intermediates and final products in real time. [Display omitted] •A novel hedgehog-like CaFe2O4 hollow microspheres were fabricated.•The photocatalytic degradation process was verified by the in situ FTIR spectra.•The gaseous toluene conversion ratio reached 76% after 8 h under mild conditions.